Electro‐Thermo Controlled Water Valve Based on 2D Graphene–Cellulose Hydrogels. (22nd May 2022) - Yang, Kou; Chen, Musen; Wang, Qian; Grebenchuk, Sergey; Chen, Siyu; Leng, Xuanye; Novoselov, Kostya S.; Andreeva, Daria V.
Abstract: Novel 2D hydrogels with coupled electro‐thermoregulation for water transport are constructed via self‐assembly of hydroxypropyl cellulose (HPC) with graphene oxide (GO) and reduced GO (rGO), where the capability of HPC to switch between hydrophobic and hydrophilic states is exploited. Amphiphilic GO surface is used to guide the ordering and alignment of liquid crystalline HPC domains. The changes in conformation and alignment of HPC serve as a switch for optical properties and water transport. A composite consisting of electrically conductive rGO and 2D hydrogel is developed to produce thermal stimulus and thus construct an electro‐thermo controlled valve for regulated water transfer. The prepared 2D hydrogel has a large swelling rate, outstanding mechanical properties (Young's modulus is 2.5 GPa), and superior electrical conductivity (176 S cm −1 ). The ability of HPC domains to change conformation in 2D confinement, when Joule heating is applied, can function as a 2D low footprint water switcher with optical control in smart membranes. The proposed sustainable approach to self‐assembly of HPC in 2D confinement of GO and rGO is applicable to the whole family of lower critical solution temperature polymers. Thus, a ubiquitous and sustainable synthesis of novel low dimensional robust multifunctional hydrogels is demonstrated. Abstract : A facile way to fabricate 2D hydrogels is proposed, consisting of graphene and cellulose derivatives. The efficiency of the material for coupled electro‐thermoresponsive water transport is demonstrated. The transfer of heat, mass, and energy can be easily controlled by the internal hydrophilic/hydrophobic switch. This approach provides prospective for fluid transport systems, actuators, and bio‐engineering solutions for smart houses.